17e0bb5ec09a7a1.png用代数法化简逻辑函数可得()
A: F=A+B
B: F=AB
C: F=B
D: F=A
A: F=A+B
B: F=AB
C: F=B
D: F=A
举一反三
- 17e0bb5eb22edc3.png用代数法化简逻辑函数可得() A: F1=AB B: F1=B C: F1=A+B
- 设F(X,A,B)为逻辑函数,且F(1,A,B)=AB,F(0,A,B)=A+B,则F等于?() A: Σ(1,2,6,7) B: Σ(0,2,3,4,5) C: Σ(1,2,3,7) D: Σ(2,3,6,7)
- 逻辑电路图如下,其逻辑表达式为_______。[img=1848x598]18034ae9e0c2388.png[/img] A: F=(A+B')(A+B) B: F=AB'+AB C: F=(AB')'+AB D: F=(A+B')'(A+B)
- 逻辑函数F=AB'CD+ABC'D'+AB'+AD'+AB'C化简为 A: AB’+AD’ B: AB+CD C: A+B D: BC+D
- 逻辑函数的最小项表达式为() A: F=Σm(0、2、5、7) B: C: F=Σm(1、3、6) D: F=Σm(0、1、2、6、7)